Linear and branched polymer prodrugs of the water-soluble nucleoside reverse-transcriptase inhibitor emtricitabine as structural materials for long-acting implants. Issue 23 (23rd May 2022) - Shakil, Anika; Hern, Faye Y.; Liu, Chung; Temburnikar, Kartik; Chambon, Pierre; Liptrott, Neill; McDonald, Tom O.; Neary, Megan; Owen, Andrew; Freel Meyers, Caren; Rannard, Steve P.
Abstract : Long acting release of the water soluble nucleoside reverse transcriptase inhibitor emtricitabine (FTC) has been demonstrated in vitro through polymer formation using FTC as a monomer, and forming implants made of the drug containing polymer. Abstract : Long-acting drug delivery is a growing area of interest as it overcomes many challenges related to patient adherence to therapy and the pill burden associated with chronic illness. Injectable formulations are becoming more common and drug-releasing implants also provide several opportunities. Highly water soluble drug compounds are poor candidates for long-acting delivery. Here, the water-soluble nucleoside reverse transcriptase inhibitor emtricitabine (FTC) has been used as a novel A–B monomer in step-growth polymerisation with chloroformate functional C n monomers, to produce new poly(carbamate/carbonate) structures with varying architecture. The polymer prodrugs were all solid at ambient temperature and have been shown to release FTC when subjected to mixed gender human plasma. Vacuum compression moulding has been used to form solid rod implants without polymer degradation; the rods show FTC release over long periods in the presence of microsomes, establishing the basis of a polymer prodrug strategy for FTC delivery.